Optimization of Process Parameters for the Production of Chitin from the Shell of Flowertail Shrimp (Metapenaeus dobsoni) - Joshy, C. G.; Zynudheen, A. A.; Ninan, George; Ronda, V.; Muhammed, Sabeena (Fishery Technology, 2016)
The objective of present study was to optimize the process parameters for the production of chitin from the shell of Metapenaeus dobsoni by deproteinization and demineralization using linear regression. The response variables viz: yield and quality of chitin were optimized in terms of concentration, treatment time and ratio of acid and alkali used in the production of chitin. First order polynomial regression model with interaction coefficients for alkali concentration with treatment time was found as optimal to explain the variability in the response variables in terms of process variables. Based on the fitted model, the coefficients of acid concentration (2.48), acid ratio (0.006) and acid treatment time (0.039) were found significant for chitin yield at 1% level and linear regression coefficients showed a non-significant increasing trend. The regression coefficient for interaction between acid concentration and treatment time showed a significant decreasing trend (-0.025). The optimum combination of process variables to improve the yield and quality of chitin from M. dobsoni shell was sodium hydroxide concentration at 3 % in 1:2 ratio and treatment time of 30 minutes and hydrochloric acid concentration at 1.25 N in1:2 ratio and treatment time of 90 minutes.